Cover Image. (22nd April 2020) - Liu, Yi; Zhang, Ye; Meng, Qi; Long, Jianglan; Wang, Man; Zhang, Xu; Yan, Can; Yan, Dan
Abstract : The cover image is based on the RESEARCH ARTICLE Metabolic profile of alkaloids in Rhizoma Coptidis in rat plasma, urine and feces after oral administration using ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry by Yi Liu et al., https://doi.org/10.1002/rcm.8763 .